HUBUNGAN KEKUATAN OTOT LENGAN DENGAN KEMAMPUAN LEMPAR LEMBING PADA SISWA SMA NEGERI 1 PURIALA - Andriawan; Asmuddin; Badaruddin (Universitas Halu Oleo, 2021)
The purpose of this study was to determine the relationship between arm muscle strength and the javelin throwing ability of students of SMA Negeri 1 Puriala. The formulation of the problem in this study is